PENGEMBANGAN LEMBAR KERJA SISWA (LKS) MATA PELAJARAN SAINS KIMIA UNTUK SMP - Rohaeti, Eli; LFX, Endang Widjajanti; Padmaningrum, Regina Tutik (Jurnal Inovasi Pendidikan, 2009)
This research was about the development of learning source in chemistry education. The aims of this research are: (1) to arrange and to develop student's working sheet on chemistry science aspect for SMP/MTs based on the education unit level curriculum (KTSP) using quality criteria and (2) to evaluate quality the student's working sheet on chemistry science aspect based on the education unit level curriculum as required by science teachers of SMP and chemistry teachers of SMA. This research included two steps: arranging and developing student's working sheet on chemistry science aspects and evaluating quality of student's working sheet. The sheet was developed based on competency standard of chemistry science aspect at grade seven and eight including (1) substance classification, (2) substance state and changes and the properties in physical and chemistry changes, (3) matter particles, (4) the usefulness of chemical material in life, and (5) addictive and psychotropical. The sheet quality was evaluated by 2 SMP science teachers and 3 SMA chemistry teachers, and then the scores were compared with ideal score. The quality criteria of the sheet were interpreted from 10 aspects. The quality of student's working sheet on chemistry science aspect for topics (1) substance classification, (2) substance state and changes and the properties in physical and chemistry changes, (3) matter particles, (4) the usefulness chemical material in life and (5) addictive and psychotropical is very good with score 98.2; 98.8; 98.4; 102.4, and 102.2 respectively or 81.8%; 82.3%; 82%, 85.3% and 85.2%.